SPECT/CT Imaging, Biodistribution and Radiation Dosimetry of a 177Lu-DOTA-Integrin αvβ6 Cystine Knot Peptide in a Pancreatic Cancer Xenograft Model - Sachindra, Sachindra; Hellberg, Teresa; Exner, Samantha; Prasad, Sonal; Beindorff, Nicola; Rogalla, Stephan; Kimura, Richard; Gambhir, Sanjiv Sam; Wiedenmann, Bertram; Grötzinger, Carsten (Frontiers in Oncology, 2021)
Introduction: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive malignant neoplasms, as many cases go undetected until they reach an advanced stage. Integrin αvβ6 is a cell surface receptor overexpressed in PDAC. Consequently, it may serve as a target for the development of probes for imaging diagnosis and radioligand therapy. Engineered cystine knottin peptides specific for integrin αvβ6 have recently been developed showing high affinity and stability. This study aimed to evaluate an integrin αvβ6-specific knottin molecular probe containing the therapeutic radionuclide 177Lu for targeting of PDAC. Methods: The expression of integrin αvβ6 in PDAC cell lines BxPC3 and Capan2 was analyzed using RT-qPCR and immunofluorescence. In vitro competition and saturation radioligand binding assays were performed to calculate the binding affinity of the DOTA-coupled tracer loaded with and without lutetium to BxPC3 and Capan2 cell lines. To evaluate tracer accumulation in the tumor and organs, SPECT/CT, biodistribution and dosimetry projections were carried out using a Capan2 xenograft tumor mouse model. Results: RT-qPCR and immunofluorescence results showed high expression of integrin αvβ6 in BxPC3 and Capan2 cells. A competition binding assay revealed high affinity of the tracer with IC50 values of 1.69 nM and 9.46 nM for BxPC3 and Capan2, respectively. SPECT/CT and biodistribution analysis of the conjugate 177Lu-DOTA-integrin αvβ6 knottin demonstrated accumulation in Capan2 xenograft tumors (3.13 ± 0.63 %IA/g at day 1 post injection) with kidney uptake at 19.2 ± 2.5 %IA/g, declining much more rapidly than in tumors. Conclusion: 177Lu-DOTA-integrin αvβ6 knottin was found to be a high-affinity tracer for PDAC tumors with considerable tumor accumulation and moderate, rapidly declining kidney uptake. These promising results warrant a preclinical treatment study to establish therapeutic efficacy.